Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Hasil Belajar Matematika di Kelas 5 SD Inpres Kinilow - Rindengan, Mersty E.; Korompis, Fransiska R.; Karundeng, Paolo Maldini (Peneliti.net, 2023)
This study aims to improve Mathematics learning outcomes in 5th grade students of SD Inpres Kinilow, through the application of the Problem-Based Learning Model. This type of research uses Classroom Action Research (PTK) Model Kemmis and Robbin MC Taggart. Research Subjects 5th grade with a total of 5 students, consisting of 4 girls and 1 boy. This research was carried out in two cycles and each cycle included four stages, namely; planning stage, implementation stage, observation stage and reflection stage. Data collection techniques in this study are observation and tests. Based on the results of research in cycle I, only 2 students were complete while 3 were incomplete or you could say that the learning outcomes in cycle I were 40%. After implementing the action in cycle II, student learning outcomes have increased, where 5 students are complete. It can be said that the learning outcomes in cycle II are 100% and have reached the Minimum Completion Criteria (KKM) of 75. Thus it can be concluded that by applying the Problem-Based Learning Model with Decimal Fraction Multiplication material can improve Mathematics learning outcomes in students in grade 5 SD Inpres Kinilow